Limitations of agile software development method inhealth care - Homayounfar, Payam (Ograniczenia metod agile tworzenia oprogramowania w sektorze zdrowia, 2011)
It became very popular in the last years to use Agile Software Development Methods (ASDM) to develop software in different areas of economy. Each new developed method aims to face new situations and solve current issues of problems for software development and project management. Each project has to be treated individually as the frame and environment conditions are different in every project and every industry. The agile approach can beuseful if it is applied in the right situation, but affects the opposite in the wrong environment. Especially the health care sector has its own specifications which lead to the limitations of agile software development methods. This paper aims to show the limitations of agile software development methods in general and health care
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 131-142
Keywords: agile software development; eXtreme Programming; Scrum; Agile Manifesto